2021
DOI: 10.3390/ijerph18147234
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Circulating MicroRNAs and the Relation of MicroRNAs to Maximal Oxygen Consumption and Intima–Media Thickness in Ultra-Marathon Runners

Abstract: The impact of long-term training on cardiovascular disease (CVD) is not clear. Carotid intima–media thickness (CIMT) test is recommended as a useful measure to diagnose the early stages of atherosclerosis. MicroRNAs (miRNAs) are altered due to endurance exercise and can be promising biomarkers of pathophysiological changes. We aimed to evaluate the association of circulating miRNAs with physical fitness and markers of atherosclerosis in ultra-marathon runners. Ultra-marathon runners had 28-fold upregulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…During the RNA extraction phase cel-miR-39 was spiked-in as an exogenous control and all qRT-PCRs were normalized to their corresponding cel-miR-39. Reactions were run in triplicate and miRNA expressions were expressed as 2-∆CT [25,75].…”
Section: Rna Preparation Detection and Quantification Of Mirnas By Qu...mentioning
confidence: 99%
“…During the RNA extraction phase cel-miR-39 was spiked-in as an exogenous control and all qRT-PCRs were normalized to their corresponding cel-miR-39. Reactions were run in triplicate and miRNA expressions were expressed as 2-∆CT [25,75].…”
Section: Rna Preparation Detection and Quantification Of Mirnas By Qu...mentioning
confidence: 99%
“…The HUNT study revealed that increased levels of miR-125a were associated with low VO 2 max in male participants, which is an indicator of cardiopulmonary fitness ( Bye et al, 2013 ). In our previous study we also found that the ultramarathon runners with the highest quartile of VO 2 max had a lower expression of miR-125a-5p ( Eyileten et al, 2021 ). In the current study we observed a negative correlation between miR-125a-5p and maximum lactate concentration.…”
Section: Discussionmentioning
confidence: 79%
“…Future research should expand to multicentric studies with larger, more diverse populations to confirm these findings and investigate the physiological mechanisms underlying the observed effects. Investigating whether cessation of SLT/Naswar use prior to interventions affects outcomes would also be valuable (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%